THE OPACITY OF THE LAW IN THE COSTA RICAN LEGAL SYSTEM. TWO SPECIFIC CASES: LEGAL PLURALISM AND LEX MERCATORIA - Cordero Molina, Sofía (2023)
The general objective of this article is to tap on two fundamental aspects visible in Carcova's book “The Opacity of Law”, and these are precisely: firstly, the maxim nemini licet ignorare jus as a legal fiction of the Costa Rican legal system. Secondly, the issue of the presence of legal pluralism in our system.  Simultaneously raised two specific cases that exemplify this particularity.